Research on the Intellectualization of Large-scale Wind Tunnel Equipment - LIAO Daxiong; CHEN Wanhua; PENG Lei; ZHANG Hao (Kongzhi Yu Xinxi Jishu)
Large-scale wind tunnel equipment, as a basic and strategic resource for aerodynamics research and the development of advanced weapons such as aerospace equipment, is a large scientific device highly integrated with multiple disciplines. Large-scale wind tunnel equipment is often characterized by complex technology, long construction period and large investment scale. In order to improve the intelligence level, flow field quality, operation efficiency and test capability of Chinese large-scale wind tunnel equipments, in this paper, intelligent measures were put forward in six aspects, including manufacture and assembly, measurement and control, compressor operation, cryobot, health management and vibration control. Furthermore, in view of the relevant key technical problems, future development directions were proposed. This paper provides references for promoting the development of wind tunnel equipment to a deep intelligent stage.